2010
DOI: 10.1080/09668130903506862
|View full text |Cite
|
Sign up to set email alerts
|

Farm Expansion in Lithuania after Accession to the EU: The Role of CAP Payments in Alleviating Potential Credit Constraints

Abstract: The impact of the introduction of EU Single Area Payments (SAP) on farm expansion strategy in Lithuania is investigated, utilizing farm accounting and survey data. The introduction of the SAP has a positive influence on farmers' intentions to expand their area compared to a baseline scenario of the hypothetical continuation of pre-accession policy. The switch in policy has a more pronounced effect on farms that were previously credit constrained. While the SAP has been presented as a support that is decoupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 29 publications
0
25
1
1
Order By: Relevance
“…According to Lorber and Žiberna [15], similar trends were also documented in Slovenia, where the number of middle-sized and large farms increased during 2002-2012. Dannenberg and Kuemmerle [16] obtained similar results for Polish farms, whereas Latruffe et al [17] arrived at the same conclusions after analyzing farm expansion in Lithuania after entry into the EU. Savickienė and Miceikienė [18] utilised the financial indicators to measure financial sustainability of Lithuanian farms.…”
Section: Introductionmentioning
confidence: 72%
“…According to Lorber and Žiberna [15], similar trends were also documented in Slovenia, where the number of middle-sized and large farms increased during 2002-2012. Dannenberg and Kuemmerle [16] obtained similar results for Polish farms, whereas Latruffe et al [17] arrived at the same conclusions after analyzing farm expansion in Lithuania after entry into the EU. Savickienė and Miceikienė [18] utilised the financial indicators to measure financial sustainability of Lithuanian farms.…”
Section: Introductionmentioning
confidence: 72%
“…Literature on access to inance in the agriculture and organic production in transitional countries is mainly focused on the supply side of the problem, usually including banks and microinance institutions. Development organizations (USAID, EBRD, OECD) are mainly dealing with the constraints and statistics, while researchers are focused on the relationship between credit supply and farm productivity, farm inputs and outputs, investments and other aspects of rural development (for details see Swinnen, Gow, 1999;Swinnen, 2007;Latruffe, 2005;Latruffe et al, 2010). It is reasonable to expect that almost all studies have found positive relationship between an increased access to inance and improvement of analyzed parameters.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…There is a wealth of research on farm investment (e.g., Bierlen & Featherstone, 1998;Benjamin & Phimister, 2002;Petrick, 2004a,b;Latruffe, 2005;Bakucs et al, 2009;Bokusheva et al, 2009;Zynch & Odening, 2009;Latruffe et al, 2010;Hüttel et al, 2010;Bojnec & Latruffe, 2011;Kallas et al, 2012). However, studies dealing with agriculture are generally limited to one country and exclude cross-country comparisons, except for Benjamin & Phimister (2002), who compared France and the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%